Combination antibiotic therapy for multidrug-resistant Gram-negative bacteria - Tängdén, Thomas (Informa Healthcare, 2014)
Combination antibiotic therapy for Gram-negative sepsis is controversial. The present review provides a brief summary of the existing knowledge on combination therapy for severe infections with multidrug-resistant Pseudomonas spp., Acinetobacter spp., and Enterobacteriaceae. Empirical combination antibiotic therapy is recommended for severe sepsis and septic shock to reduce mortality related to inappropriate antibiotic treatment. Because definitive combination therapy has not been proven superior to monotherapy in meta-analyses, it is generally advised to de-escalate antibiotic therapy when the antibiotic susceptibility profile is known, although it cannot be excluded that some subgroups of patients might still benefit from continued combination therapy. Definitive combination therapy is recommended for carbapenemase-producing Enterobacteriaceae and should also be considered for severe infections with Pseudomonas and Acinetobacter spp. when beta-lactams cannot be used. Because resistance to broad-spectrum beta-lactams is increasing in Gram-negative bacteria and because no new antibiotics are expected to become available in the near future, the antibacterial potential of combination therapy should be further explored. In vitro data suggest that combinations can be effective even if the bacteria are resistant to the individual antibiotics, although existing evidence is insufficient to support the choice of combinations and explain the synergistic effects observed. In vitro models can be used to screen for effective combinations that can later be validated in animal or clinical studies. Further, in the absence of clinical evidence, in vitro data might be useful in supporting therapeutic decisions for severe infections with multidrug-resistant Gram-negative bacteria.